Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0054134
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Models of Adult Pacific Salmon Returns

Abstract: Most modeling and statistical approaches encourage simplicity, yet ecological processes are often complex, as they are influenced by numerous dynamic environmental and biological factors. Pacific salmon abundance has been highly variable over the last few decades and most forecasting models have proven inadequate, primarily because of a lack of understanding of the processes affecting variability in survival. Better methods and data for predicting the abundance of returning adults are therefore required to eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 40 publications
4
99
0
Order By: Relevance
“…Additionally, rockfish growth and seabird reproductive success has been related to winter ocean conditions, particularly during February (Black et al 2010). Logerwell et al (2003) and Burke et al (2013) observed significant relationships between juvenile salmon marine survival and ocean conditions during the winter prior to ocean entry. The link between biological performance measures and winter ocean conditions has not been limited to predators; winter ocean conditions have also been associ- ated with the early life history stages of other fishes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, rockfish growth and seabird reproductive success has been related to winter ocean conditions, particularly during February (Black et al 2010). Logerwell et al (2003) and Burke et al (2013) observed significant relationships between juvenile salmon marine survival and ocean conditions during the winter prior to ocean entry. The link between biological performance measures and winter ocean conditions has not been limited to predators; winter ocean conditions have also been associ- ated with the early life history stages of other fishes.…”
Section: Discussionmentioning
confidence: 99%
“…For juvenile salmon, ichthyoplankton biomass during the winter prior to ocean entry explains 34 to 85% of the variability in marine survival or adult returns. Burke et al (2013) used a multivariate model with 31 environmental and biological processes to predict spring Chinook salmon stock specific adult return and the most important indicators were bottom-up processes including the winter ichthyoplankton data set. Most of the indicators used in the Burke et al (2013) model relied on environmental or biological factors that are typically available or measured in late spring or summer after the hatchery salmon juveniles have been released.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include interannual variation in pollock recruitment in the Eastern Bering Sea Eisner et al, 2014), interdecadal fluctuations in salmon marine survival across the Northeast Pacific (Mantua et al, 1997;Hooff and Peterson, 2006;Burke et al, 2013), and long-term trends in forage fish and seabird abundance in the North Sea (Beaugrand and Kirby, 2010;MacDonald et al, 2015). These cases can be all be schematized as following the "junk food" hypothesis (Österblom et al, 2008) in which the crucial axis of variation is not between high and low total prey productivity, but rather between high and low relative abundance of large, lipid-rich prey taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, an ecosystem metric approach using ranks and multiple indicators was developed to provide a qualitative pink salmon harvest outlook. This use of multiple ecosystem indicators (oceanographic and ecological) has been described previously to forecast returns of other salmonids such as Chinook salmon (O. tshawytscha) and coho salmon (O. kisutch) in the Pacific Northwest in multivariate or "stoplight" chart approaches (Logerwell et al 2003;Burke et al 2013;Peterson and Burke 2013).…”
Section: Introductionmentioning
confidence: 99%